2019
DOI: 10.1177/2470547019875116
|View full text |Cite
|
Sign up to set email alerts
|

Hair Cortisol Concentration and Mental Disorder in Children With Chronic Physical Illness

Abstract: Background To examine changes in hair cortisol concentrations (HCC) in children with chronic physical illness and identify patterns of association between HCC and mental comorbidity. Methods A sample of 50 children aged 6 to 16 years were recruited within six months of being diagnosed with a chronic physical illness. Data were collected via hair samples, structured interviews, and behavioral checklists. Results There was no change in HCC over six months. Baseline HCC was associated with internalizing—odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…22 The protocol for hair processing was based on that of Vaghri et al 23 and has been previously used successfully. 11,24 Samples were analyzed using enzyme-linked immunosorbent assay (ELISA) using the High Sensitivity Salivary Cortisol Immunoassay Kit (Cat# 1-3002, Salimetrics, Pennsylvania).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The protocol for hair processing was based on that of Vaghri et al 23 and has been previously used successfully. 11,24 Samples were analyzed using enzyme-linked immunosorbent assay (ELISA) using the High Sensitivity Salivary Cortisol Immunoassay Kit (Cat# 1-3002, Salimetrics, Pennsylvania).…”
Section: Methodsmentioning
confidence: 99%
“…9,10 This is also evident in the context of physical illness whereby HPA dysregulation, as measured by hair cortisol concentration (HCC), was found to be associated with the onset of mental disorder in children and adolescents with physical illness. 11 The extent to which cortisol is associated with HRQoL in children and adolescents is unclear. One study found no association between HCC and HRQoL among healthy children, 12 and the second found a positive association between HCC and HRQoL only among high-risk children whose mothers had been exposed to early-life maltreatment (ie, moderating effect).…”
Section: Introductionmentioning
confidence: 99%
“…Hair will be collected using a standardised approach by research staff from children/youth and parents by cutting approximately 80 strands (roughly 4 mm diameter) from the posterior vertex of the head, as close to the scalp as possible. the extraction and assaying of cortisol will follow established procedures, which we have also used previously 34. Variables hypothesised to affect hair cortisol concentration (eg, hair washes, medications, smoking behaviour (including exposure to secondhand smoke)) will be collected via parent report on a separate form 67 71 72…”
Section: Methodsmentioning
confidence: 99%
“…the extraction and assaying of cortisol will follow established procedures, which we have also used previously. 34 Variables hypothesised to affect hair cortisol concentration (eg, hair washes, medications, smoking behaviour (including exposure to secondhand smoke)) will be collected via parent report on a separate form. 67 71 72 While parents are completing study questionnaires, children 2-5 years will complete the Peabody Developmental Motor Scales, second edition (PDMS-2) to assess gross motor development.…”
Section: Biological Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation